PENINGKATAN KOMPETENSI GURU MELAKSANAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING MELALUI SUPERVISI KLINIS - Sukamsinah; Rahmat Mulyono (STKIP Subang, 2022)
This study aims to improve teacher competence in implementing the Problem Based Learning learning model through clinical supervision in class III SD Negeri Percobaan 4 in 2020. The study was conducted from January to April 2020 with 2 target teachers as research subjects. The mentoring is carried out using a cycle design model to the Kemmis Tagart cycle. The research was conducted in two cycles, each cycle through four stages of activities, namely Planning, Implementation, and Reflection. The results showed that through the supervision of teacher competence in compiling lesson plans containing problem-based learning models and implementing learning using problem-based learning models, the percentage increased at each stage, from Pra-Siklus Kategori Kurang (62.5), siklus I Kategori Cukup (74), Siklus II Kategori Baik (90). Thus, the results of this study indicate that the application of clinical supervision can improve the ability of teachers in preparing lesson plans and implementing Problem Based Learning learning models in SD Negeri Percobaan 4 Kapanewon Wates, Kulon Progo Regency.